THE INFLUENCE OF KNOWLEDGE AND PERCEPTIONS OF BUDGET MANAGEMENT AND LEADERSHIP STYLE ON CHANGES IN BUDGET IMPLEMENTATION AT HOSPITAL "X" - Mirnawati A; Andarini, Sri; Holipah, Holipah (Journal of Community Health and Preventive Medicine, 2025)
Hospital "X" as a Regional Public Service Agency (BLUD) has flexibility in financial management including the expenditure budget. In the budget implementation process over the past five years (2019-2023), there have often been changes in its implementation with an average adjustment of IDR 273,182,832,504 or 39.60% of the total allocated budget each year. Given the situation, this research aims to analyze the influence of knowledge and perceptions about budget management and leadership style on changes in budget implementation. The data was collected through questionnaires distributed to 42 heads of work units and secondary data taken from the 2019-2023 budget utilization documents. Data analysis was conducted using multiple linear regression tests to determine the influence of knowledge and perceptions of budget management, as well as leadership style on changes in budget implementation. The results of the research show that the higher the knowledge and the more accurate the perception of budget management among the heads of the work unit, the lower the changes in the implementation of the hospital budget. However, there is no influence of leadership style on changes in hospital budget implementation. In addition, knowledge and perceptions about budget management and leadership style simultaneously influence changes in the hospital budget. Knowledge, perception, and leadership style can influence changes in budget implementation with a contribution of 35.30%, while the remaining contribution of 64.70% is influenced by other factors not examined in this research. In conclusion, the factors that influence changes in the implementation of hospital budgets are knowledge and perceptions about budget management. Leadership style, on the other hand, is not a determining factor, since changes in hospital budget implementation remain high despite most heads of work units adopting a democratic leadership style.